Global Reserve Optimization Method Considering Resources and Output Characteristics of Renewable Energy - Qian CAI; Jing WANG; Tianxiang GENG; Feng LI; Tiandong MA (Zhongguo dianli)
A global reserve optimization technology based on trans-regional UHVDC transmission channels was presented, which takes into account the complementary characteristics and the predicted output characteristics of renewable energy resources. Firstly, the correlation and complementary characteristics of renewable energy resources in China were analyzed, and the feasibility of complementary operation of overall resources in different regions was studied. Then, a real-time reserve optimization technology based on statistical characteristics of renewable energy prediction was proposed, and a trans-regional global reserve optimization technology based on time series production simulation method was established. Finally, taking “Three North” regions as an example, the case study of global reserve optimization considering the complementary characteristics of regional resources was carried out. The case results show that the method proposed in this paper optimizes the startup mode of conventional thermal power units, and can realize the reasonable optimization of real-time reserve, promote the accommodation of renewable energy, and improve the overall operation efficiency of the power grid.